The Complement System of Agnathans - Matsushita, Misao (Frontiers in Immunology, 2018)
Agnathans (lamprey and hagfish) are a group of primitive jawless fish. Jawed vertebrates possess adaptive immunity including immunoglobulins, while agnathans lack immunoglobulins but have alternative adaptive immunity in which variable lymphocyte receptors (VLRs) function as antibodies. The complement system consists of many proteins involved in the elimination of pathogens. In mammals, it is activated via the three different pathways, resulting in the generation of C3b followed by the lytic pathway. Complement components including C3, MBL and MASP of the lectin pathway and factor B of the alternative pathway have been identified from lamprey and/or hagfish, while lytic pathway components have not been identified. In mammals, C1q binds to IgM/IgG-antigen complexes and activates the classical pathway in association with C1r and C1s. Lamprey also has C1q (LC1q) but its function differs from that of mammalian C1q. LC1q acts as a lectin and activates C3 in association with MASP via the lectin pathway. Furthermore, LC1q may interact with a secreted type of VLR (VLRB) in complex with antigens, and mediate activation of C3, potentially via MASP, leading to cytolysis. Cytolysis is mediated by a newly identified serum protein named lamprey pore-forming protein (LPFP). In conclusion, lamprey has a complement activation pathway, which could be regarded as the classical pathway, and also has a cytolytic system that is distinct from the mammalian lytic pathway. Thus, it appears that the complement system of agnathans is very unique and may have developed independently from jawed vertebrates.